The Red Door Inn - Johnson, Liz 1981- (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2016)
"Marie Carrington is running from a host of bad memories. Broke and desperate, she's hoping to find safety and sanctuary on Prince Edward Island, where she reluctantly agrees to help decorate a renovated bed-and-breakfast before it opens for prime tourist season. Seth Sloane didn't move three thousand miles to work on his uncle's B&B so he could babysit a woman with a taste for expensive antiques and a bewildering habit of jumping every time he brushes past her ... The only thing Marie and Seth agree on is that getting the Red Door Inn ready to open in just three months will take everything they've got. Can these two wounded souls find hope, healing, and perhaps a bit of romance on this beautiful island?"--Amazon.com.
Keywords: Bed and breakfast accommodations -- Fiction; Man-woman relationships -- Fiction; Prince Edward Island -- Fiction; Christian fiction; Romance fiction